The Canva Application; Solutions For Development Of Learning Media for Islamic Religious Education at SDN 10 Perembang Gala, Indonesia - Saribujang; Sukino; Erwin Mahrus (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This study aimed to analyze the learning of Islamic Religious Education and BP in elementary schools in an engaging, fun, and not dull learning. This study uses the Research and Development (R&D) research method, and the model used is the ADDIE development model. Media experts have validated this product and tested it with ten students of SD 10 Perembang Gala village of Landau Tubun, Malawi. Primary data sources are Islamic Religious Education teachers, students, and school principals; secondary data sources include research journals, books, and websites. This study's results indicate that the validation results show that media experts get an average of 78.75%, which is included in the